Redka vrsta raka jajčnikov pri mladih bolnicah s slabo napovedjo izida bolezni - Šturm Indihar, Blažka (Medicinski razgledi, 2022)
Small cell ovarian carcinoma of the hypercalcemic type is a very rare and aggressive malignant disease. It occurs more often in young women of childbearing age, before the age of 40. It is associated with a germline or a somatic mutation of the SMARCA4 (SWitch/sucrose non-fermentable related, matrix associated, actin dependent regulator of chromatin, subfamily a, member 4) gene, which encodes the eponymous protein. The before-mentioned protein is part of the chromatin complex, which plays an important role in cellular processes such as DNA repair and transcription, as well as in cell differentiation and division. The defective protein is said to contribute to the formation and progression of cancer. The literature describes less than 500 cases of small cell ovarian cancer of the hypercalcemic type. Hypercalcemia is present in 60% of the cases. The prognosis is extremely poor due to non-characteristic signs and symptoms, which initially appear with abdominal symptoms. Overall survival in the initial stages is only 30%. The pathohistological examination of the neoplasm must be performed by an experienced pathologist, as a wrong diagnosis can lead to inadequate treatment. Many treatment and follow-up approaches have been proposed but unfortunately, given the extreme rarity of the disease, there is still no coordinated approach. The purpose of the article is to emphasize the importance of treatment planning and fertility preservation in the mentioned type of cancer. The case of a young patient with small cell ovarian cancer of the hypercalcemic type with uncharacteristic symptoms is presented.
Keywords: jajčniki; rak (medicina); tumor